Pengetahuan Pajak, Pelayanan Pajak, Sanksi Pajak,Kesadaran Wajib Pajak, Dan Sosialisasi Pajak Dan Kepatuhan Pembayaran Pajak Bumi Dan Bangunan - Sapto Bayu Aji; Budhi Purwantoro Jati; Budi Asmarawati (MEASUREMENT : Jurnal Program Studi Akuntansi, 2024)
This study aims to determine and analyse the effect of tax knowledge, tax services, tax sanctions, and taxpayer awareness on taxpayer compliance in paying land and building tax. The object of research is land and building taxpayers in the Special Region of Yogyakarta. The sample in this method uses purposive sampling. The research uses quantitative data methods obtained by distributing research questionnaires directly to 120 respondents as Land and Building Taxpayers. The test results show that tax knowledge, tax services, tax sanctions, and taxpayer awareness have no effect on taxpayer compliance in land and building tax payments. While tax socialisation affects taxpayer compliance in the payment of land and building tax.